2014
DOI: 10.1002/cctc.201301051
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Study of Ni‐catalyzed Carbon Dioxide Coupling with Ethylene towards the Manufacture of Acrylic Acid

Abstract: The reaction mechanism of CO2 coupling with C2H4 by homogeneous Ni‐complexes bearing bidentate phosphorous ligands was studied by means of density functional theory calculations. The reaction is initiated by sequential coordination of C2H4 and CO2 to the Ni center, followed by a facile coupling step, which results in a stable nickelalactone intermediate. Subsequent decomposition of this intermediate through β‐H transfer is the rate‐determining step. Together with the following reductive elimination step to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Further attempts were made by various groups to enrich our mechanistic understandings, including the thermodynamic aspects for the low catalytic activity, other plausible reaction pathways, the importance of the steric and electronic properties of the ligands, the solvent effects, and the elongation of the Ni−O bond by addition of MeI, thereby lowering the energy barrier for β‐H elimination. Effects of other additives such as Lewis acids, bases, and certain cations were also considered in various computational modeling studies. Not surprisingly, even for the nickel‐based catalytic system, the exact CO 2 –ethylene carboxylation mechanism is still under debate.…”
Section: Introductionmentioning
confidence: 64%
“…Further attempts were made by various groups to enrich our mechanistic understandings, including the thermodynamic aspects for the low catalytic activity, other plausible reaction pathways, the importance of the steric and electronic properties of the ligands, the solvent effects, and the elongation of the Ni−O bond by addition of MeI, thereby lowering the energy barrier for β‐H elimination. Effects of other additives such as Lewis acids, bases, and certain cations were also considered in various computational modeling studies. Not surprisingly, even for the nickel‐based catalytic system, the exact CO 2 –ethylene carboxylation mechanism is still under debate.…”
Section: Introductionmentioning
confidence: 64%
“…Calculations pointed towards a similar reaction pathway for L1 and other modified bipyridines and bidentante phosphines, even though with different energetic profiles. Further theoretical studies were carried with other different ligands, leading to similar conclusions [70]. Interestingly, in 2014, Limbach et al theoretically proposed two different modes of addition of CO 2 into the Ni(0) ethylene intermediates with bidentate phosphine ligands, consisting of an inner sphere and outer sphere mechanism (Scheme 15, b) [71].…”
Section: Stoichiometric Processes Involving Alkenesmentioning
confidence: 67%
“…Recently, Schaub et al discovered that formation of carbonic acid half-esters could be avoided by increasing the temperature up to 145°C, successfully obtaining catalytic turnover for the non-iterative carboxylation process [97]. In 2014, Pidko exhaustively studied this catalytic transformation in the presence of different bidentate phosphine ligands using DFT calculations [70]. Although this study confirmed the important role of the ligand on nickelalactone formation, there was a marginal electronic, geometric, or steric effect of the ligand on the catalytic activity.…”
Section: = I Otfmentioning
confidence: 99%
“…By repeating these steps a TON of greater than 10 was achieved, which marked an important step in possibly turning this so-called dream reaction into a viable process. Within a short period of time, several theoretical and mechanistic studies were carried out based on the findings of this exciting process and the role of alkaline metal cations in the cleavage of the lactone, which demonstrate the significant interest this report has created [63][64][65].…”
Section: Nickel-catalyzed Reactionsmentioning
confidence: 89%